2020
DOI: 10.7759/cureus.7239
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Classification of Thyroid Nodules: A Systematic Review

Abstract: Ultrasound (US) based classification systems exist for the stratification of thyroid nodules based on the risk for malignancy. This systematic review aimed to assess the evidence for the performance of US-based thyroid nodule classification systems through correlation with fine needle aspiration biopsy (FNAB). PubMed and Scopus were searched using keywords that included 'ultrasound classification', 'thyroid nodules', 'fine needle aspiration', and 'malignancy'. Inclusion criteria were as follows: studies/review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…comet tails are typically within, or at the edge of, the follicle; whereas microcalcifications occur scattered in solid tissue. 34,35 Occasionally, it can be difficult to distinguish the density of a comet tail from a microcalcification, leading to divergent opinions on how reassuring it is to observe the density of a comet tail within a nodule. Studies of thyroid ultrasound have shown that the harmonic option (display mode on ultrasound machine) improves the structural image quality of the colloid nodules in 75-85% of cases.…”
Section: European Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…comet tails are typically within, or at the edge of, the follicle; whereas microcalcifications occur scattered in solid tissue. 34,35 Occasionally, it can be difficult to distinguish the density of a comet tail from a microcalcification, leading to divergent opinions on how reassuring it is to observe the density of a comet tail within a nodule. Studies of thyroid ultrasound have shown that the harmonic option (display mode on ultrasound machine) improves the structural image quality of the colloid nodules in 75-85% of cases.…”
Section: European Endocrinologymentioning
confidence: 99%
“…Nodules with large comet-tail artefacts, especially those around a cystic nodule, are almost always a benign lesion. 34 A biopsy can be remarkably avoided in most of these lesions unless other suspect features are present. 27 Therefore, radiologists need to systematically master the characteristics of the thyroid nodules to produce a reliable result.…”
Section: European Endocrinologymentioning
confidence: 99%
“…Specific ultrasound characteristics of thyroid tumors, such as hypoechogenicity, taller-than-wide shape on transverse view, irregular margins, microcalcifications/echogenic foci, and apparent extrathyroidal extension are associated with malignancy. These and other ultrasound features have been employed by various professional societies to develop ultrasound risk assessment schemes to select thyroid nodules for FNA biopsy [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Neck ultrasonography is the first-line imaging procedure, which is able to identify and classify the risk of the thyroid nodules [ 9 , 10 , 11 ]. Adult-based neck US risk stratification systems (RSSs) have been developed in recent years to integrate the US features in an effort to improve diagnostic accuracy and as an aid in the stratification of the risk of malignancy [ 9 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%